PERANCANGAN INTERIOR SARANA SIMULASI MITIGASI BENCANA ALAM DI KABUPATEN GIANYAR, BALI - I Kadek Widiana; I Gusti Agung Haryawan; I Putu Gede Suyoga (LPPM Institut Desain dan Bisnis Bali, 2019)
Natural disasters that often occur in Indonesia are caused by the geographical position of Indonesia which is at the confluence of three large tectonic plates that are interlocking and there is a buildup of energy. When the rock can no longer hold that energy, there will be a spontaneous release of energy that is felt as an earthquake. The earthquake can cause a tsunami if a plate breaks on the seabed. As a result, natural disasters that occur in Indonesia such as earthquakes and tsunamis often cause fatalities due to the lack of education to the public about the importance of natural disaster mitigation. Submission of education on natural disaster mitigation has been carried out by relevant parties in Bali by conducting simulations to educational institutions to the general public. However, the process of delivering this education has not been carried out comprehensively, so that many people still do not understand how to recognize signs and procedures for rescuing themselves in the event of a natural disaster. Therefore, there is a need for a means of conducting an education process on the importance of natural disaster mitigation in the form of facilities for simulation and training. The focus of this writing is the interior design of natural disaster mitigation simulation facilities located in Gianyar Regency, Bali by applying a theme based on the local wisdom of Balinese culture and applying the concept of